Dragons in the land of the condor : writing tusán in Peru - López-Calvo, Ignacio (The University of Arizona Press, 2014)
"The book considers the influence of a Chinese ethnic background or lack thereof in the writing of several twentieth and twenty-first century Sino-Peruvian authors"--